Chlorido[1-(2-oxidophenyl)ethylidene][tris(3,5-dimethylpyrazol-1-yl)hydroborato]iridium(III) chloroform monosolvate - Santos, Laura L. (International Union of Crystallography, 2013)
In the title compound, [Ir(C(15)H(22)BN(6))(C(8)H(7)O)Cl]·CHCl(3), the Ir atom is formally trivalent and is coordinated in a slightly distorted octahedral geometry by three facial N atoms, one C atom, one O atom and one Cl atom. The Ir=C(carbene) bond is strong and short and exerts a notable effect on the trans-Ir—N bond, which is about 0.10 Å longer than the two other Ir—N bonds. The chloroform solvent molecule is anchored via a weak C—H⋯Cl hydrogen bond to the Cl atom of the Ir complex molecule. In the crystal, the constituents adopt a layer-like arrangement parallel to (010) and are held together by weak intermolecular C—H⋯Cl hydrogen bonds, as well as weak Cl⋯Cl [3.498 (2) Å] and Cl⋯π [3.360 (4) Å] interactions. A weak intramolecular C—H⋯O hydrogen bond is also observed.